Elastic, strong and tough ionically conductive elastomers - Burebi Yiming; Simon Hubert; Alex Cartier; Bruno Bresson; Gabriel Mello; Armelle Ringuede; Costantino Creton (Nature Communications)
Abstract Stretchable elastic materials with high strength, toughness, and good ionic conductivity are highly desirable for wearable devices and stretchable batteries. Unfortunately, limited success has been reported to attain all of these properties simultaneously. Here, we report a family of ionically conductive elastomers (ICEs) without compromise between mechanical properties (high stiffness, reversible elasticity, fracture resistance) and ionic conductivity, by introducing a multiple network elastomer (MNE) architecture into a low $${T}_{g}$$ T g polymer. The ICEs with the MNE architecture exhibit a room temperature ionic conductivity of the order of $${10}^{-6}\,{{{\rm{S}}}.{{\rm{cm}}}}^{-1}$$ 10 − 6 S . cm − 1 and stress at break of ~8 MPa, whereas the simple networks without an MNE architecture show two orders magnitude lower ionic conductivity ( $${10}^{-8}\,{{{\rm{S}}}.{{\rm{cm}}}}^{-1}$$ 10 − 8 S . cm − 1 ) and comparably low strength (<1.5 MPa) at 25 °C than their MNE architecture based counterparts. The MNE architecture with a low $${T}_{g}$$ T g monomer combines the stiffness and fracture toughness given by sacrificial bond breakage while improving ionic conductivity through increased segmental mobility.